Faktor-Faktor Yang Berhubungan Dengan Kejadian Hipertensi Di Puskesmas Bintuhan Kabupaten Kaur Tahun 2022 - Sianturi, Saidah; Fauzi, Yusran; Darmawansyah, Darmawansyah (Journal Hygeia Public Health, 2022)
There are 1712 people with hypertension in Kaur Regency in 2020. (Kaur District Health Office, 2020). Data from the Bintuhan Health Center in Kaur Regency show that there will be 138 people with hypertension in 2020 and 147 people in 2021. Knowing the factors associated with the incidence of hypertension at the Bintuhan Health Center, Kaur Regency in 2022. This study used a descriptive quantitative research type with an analytic survey research method using a Cross Sectional design using a total sampling technique with a sample of 76 respondents. The research instrument uses a questionnaire sheet. The research analysis used univariate and bivariate analysis with the chi square test. The results showed that there was a relationship between age (p value=0.022), family history (p value=0.012), knowledge (p value=0.005), obesity (p value=0.015) and the incidence of hypertension at the Bintuhan Health Center, Kaur District in 2022. there is an increase in health promotion by health workers in the community regarding improving the quality of life through healthy living behaviors and avoiding risk factors for hypertension.